THE EFFECT OF THE POLRI PRESISI PROGRAM AND DIGITAL COMPETENCE ON FIELD SERVICE PERFORMANCE AT THE DIRECTORATE OF SAMAPTA, LAMPUNG REGIONAL POLICE - Eca Viktriani; Hendri Dunan (International Journal of Multidisciplinary Reseach, 2026)
Field service performance determines the quality of professional, responsive, and community-oriented policing. This study analyzes the partial and simultaneous effects of the Polri Presisi Program and digital competence on field service performance at the Directorate of Samapta, Lampung Regional Police. A quantitative survey was conducted using saturated sampling of 68 personnel. Data were collected through a five-point Likert questionnaire and analyzed with descriptive statistics and multiple linear regression using IBM SPSS. The Polri Presisi Program had a positive and significant effect on field service performance (B = 0.328; t = 2.931; p = 0.005). Digital competence also had a positive and significant effect (B = 0.720; t = 6.974; p < 0.001) and was the dominant predictor (β = 0.679). Both variables simultaneously affected performance (F = 284.126; p < 0.001) and explained 89.7% of its variance. Strengthening field services therefore requires consistent Presisi implementation integrated with continuous digital competence development.